Static series-connected compensator with control of load-side using three single-phase H-bridge inverters - K. Daychosawang (2018)
In this paper, a static series-connected compensator with load-side connected shunt converter and a voltage sag detection control strategy are proposed. The proposed system uses three single-phase H-bridge inverters with the unipolar pulsewidth modulation technique. The control strategy for the series converter is based on the transport delay phase-locked loop for each phase in a three-phase system. The aim of this research is to improve the voltage restoration of static series-connected compensator, by which the voltage on the load-side can be restore under voltage sag condition as well as normal condition including symmetrical and asymmetrical voltage sags. The simulation results confirm the feasibility of the proposed system which was compared with the supply-side connected shunt converter of the static series-connected compensator for both symmetrical and asymmetrical voltage sag conditions. © 2013 IEEE.